Effect of Ce Addition on the Magnetoresistivity, Irreversibility Field, Upper Critical Field and Activation Energies of Bi-2212 Superconducting Ceramics - Yıldırım, Gürcan; Doğruer, Musa; Öztürk, Özgür; Varilci, Ahmet; Terzioğlu, Cabir; Zalaoğlu, Yusuf (Springer Science and Business Media LLC, 2011)
This study aims to analyze the effect of Ce addition on the microstructural, superconducting and physical properties of Bi1.8Sr2.0Ce x Ca1.1Cu2.1O y ceramics with x=0, 0.001, 0.003, 0.005, 0.01, 0.03, 0.05 and 0.1 via X-Ray analysis (XRD), scanning electron microscopy (SEM), electron dispersive X-Ray (EDX) and magnetoresistivity measurements. The ceramics produced in this work are prepared using the standard solid-state reaction method. The zero resistivity transition temperatures (T c), activation energies (U 0), irreversibility fields (μ 0 H irr) and upper critical fields (μ 0 H c2) are determined from the resistivity versus temperature (R–T) curves under dc magnetic fields up to 7 T. The results show that T c and U 0 values of the samples are found to decrease dramatically with the increase in the Ce-content and applied magnetic field. Moreover, XRD results indicate that all the samples contain the Bi-2212 phase only and exhibit the polycrystalline superconducting phase with less intensity of diffraction lines with the increase of the Ce addition. As for the results of SEM images, the texturing, crystallinity, grain size distribution, layered grain growth and grain connectivity are observed to degrade with the increase of the Ce doping. Besides, the irreversibility fields and upper critical fields are found to degrade as Ce doping increases. Penetration depths (λ) and coherence lengths (ξ) are also discussed.
Keywords: Magnetoresistivity; Activation Energy; Irreversibility Field; Bi1.8Sr2.0CexCa1.1Cu2.1Oy; Upper Critical Field